The Efficacy of Entrepreneurship Orientation on SMEs' Performance - Solomon Akpoviroro Kowo; Popoola Mufutau Akanmu (Journal of Islamic Economic and Business Research, 2021)
Entrepreneurial Orientation is a key source of intangible value for organizations to sustain the competitive advantage through highlighting the new opportunities available in the business environment, exploiting them optimally and making them successful especially in a highly competitive business environment. EO has emerged as an area of research and EO impact studies have become a sub-field in Entrepreneurship Education research. The objectives of the study are to determine the effect of Organizational Culture on EO and also to examine the effect of Entrepreneurship Orientation (EO) on firm performance. The study population refers to the managers of SMEs that are registered with the Small and Medium Enterprises Development Agency of Nigeria (SMEDAN) in Lagos State. Analysis of variance (ANOVA), correlation efficient and regression analysis was adopted. The research found that organizational culture is EO driven. Entrepreneurial orientation can be supported through organizational culture hence; organizational culture may have the capability to influence SMEs performance and therefore can lead to enhancement in competitiveness. The study also found a positive relationship between EO and firm performance which can be interpreted by the fact that a high EO level in firms shows that the firm is highly innovative, proactive and capable of undertaking risky activities. The study recommends that Entrepreneurial Orientation should be encouraged in the SME sector by undertaking different policy measures, there by resulting in better performance. The firm’s performance can be leveraged to enhance organizational learning processes, creative performance, corporate performance, improved decision making processes and adaptation to a rapidly changing work environment.